2016
DOI: 10.1080/14767058.2016.1228055
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of interleukin-6 (IL-6) and erythropoietin (EPO) in umbilical cords of preterm infants with intraventricular hemorrhage in two hospitals in Tehran

Abstract: The concentration of IL-6 and EPO levels of the cord plasma was higher in the premature newborns with IVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Second, our current study, like many of the studies on human recurrent pregnancy loss, has still not demonstrated a direct cause-and-effect relationship between the inflammatory event and pregnancy loss; for instance, an inflammatory maternal response to a fetus that has died due to non-immunological factors, could well manifest the IL-6 secretion in CD4+ T cells and/or the production of other inflammatory cytokines at the maternal–fetal interface. However, given the association between IL-6 dysregulation and pregnancy failure, and the previously demonstrated deleterious effects of IL-6 on the conceptus and the fetal [ 41 , 42 ], it is suggested that IL-6-mediated effects may have been the cause of pregnancy failure in at least a proportion of the cases. Additional studies will be needed to confirm causality and determine the mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our current study, like many of the studies on human recurrent pregnancy loss, has still not demonstrated a direct cause-and-effect relationship between the inflammatory event and pregnancy loss; for instance, an inflammatory maternal response to a fetus that has died due to non-immunological factors, could well manifest the IL-6 secretion in CD4+ T cells and/or the production of other inflammatory cytokines at the maternal–fetal interface. However, given the association between IL-6 dysregulation and pregnancy failure, and the previously demonstrated deleterious effects of IL-6 on the conceptus and the fetal [ 41 , 42 ], it is suggested that IL-6-mediated effects may have been the cause of pregnancy failure in at least a proportion of the cases. Additional studies will be needed to confirm causality and determine the mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…This speculation is supported by previous reports that the cord serum level of IL-6 is a significant predictor of the severity of the hypoxic-ischemic encephalopathy and IVH in preterm neonates. 24,25 An important finding of this study is that elevated C5a cord plasma levels at birth were independently associated with vision-threatening ROP requiring laser treatment after adjusting for important clinical factors, including gestational age at birth and birth weight. To our knowledge, this is the first study that describes changes in cord plasma levels of complement activation fragments at birth in relation to the postnatal development of ROP.…”
Section: Discussionmentioning
confidence: 75%
“…(2012), свидетельствующих о снижении уровня IL-6 в пуповинной крови детей с БЛД тяжелой степени, в проведенном нами исследовании отмечалось его повышение на уровне тенденции. Некоторые авторы связывают высокие уровни IL-6 при рождении с развитием синдрома воспалительной реакции плода и неблагоприятным неонатальным исходом [13], ранними пери/ интравентрикулярными кровоизлияниями [15] и сепсисом у недоношенных детей [16]. По нашему мнению, повышение уровня IL-6 в пуповинной крови может явиться следствием перенесенной гипоксии, внутриутробной инфекции [10].…”
Section: Discussionunclassified